ANALISIS PENGARUH PERKEMBANGAN BANTUAN ASING (FOREIGN AID), INVESTASI ASING DAN EKSPOR TERHADAP PERTUMBUHAN PENDAPATAN INDONESIA, 200.1-2008.4. : DENGAN ANALISIS MODEL DINAMIK - Heru Irianto (Universitas Sebelas Maret, 2010)
Purpose of this paper will study foreign aid, foreign investment and export to growth of chartered investment counsel Indonesia at time line from the year 2000.1 up to 2008.4, with analysis dynamic. Test result stationary data and cointergration shows that stationary data but is not cointergration to be used of VAR in level. Further of result analysis of Var Method which is executed to show that modeling which is bulit that is growth of influence foreign aid (LFA), foreign capital investment (LPM) and export (LEX) have is true. Based on analysis of variant decomposition seen the influencing growth is growth variable (Lg) it self, medium of foreign aid variable (LFA), foreign investment (LPM) and variable exports (LX) its the influence very low. Based on analysis of impulse response is found by that influence foreign aid variable (LFA) strongest are compared to by foreign investment variable (LPM) and variable exports (LX).